2020
DOI: 10.1007/s12685-020-00254-4
|View full text |Cite
|
Sign up to set email alerts
|

The valens aqueduct of constantinople: hydrology and hydraulics

Abstract: A hydrological and hydraulic engineering analysis has been carried out on the Valens aqueduct system constructed from around AD 345 and serving Constantinople. A GIS analysis of previous field observations combined with a digital elevation model confirmed the aqueduct’s likely route and slope. Macrophysical Climate Modelling revealed that contemporary weather data was an appropriate proxy for the time of the aqueduct’s construction, and modern flow data was obtained for some of the springs that fed the aqueduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The capacity of similar hydraulic analysis to shed insight on Roman water engineering design practice has been made clear, in particular by Ortloff's CFD work on Ephesus (Ortloff et al 2001) and Petra (Ortloff 2014), by Haut et al (2007) on Apamea and by Motta et al (2017) on Rome's Aqua Anio Novus, and on specific issues of system configuration, as demonstrated by work on Constantinople (Crapper 2020) and Pompeii (Monteleone et al 2021). These approaches are commended where there is sufficient physical evidence on which to base them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The capacity of similar hydraulic analysis to shed insight on Roman water engineering design practice has been made clear, in particular by Ortloff's CFD work on Ephesus (Ortloff et al 2001) and Petra (Ortloff 2014), by Haut et al (2007) on Apamea and by Motta et al (2017) on Rome's Aqua Anio Novus, and on specific issues of system configuration, as demonstrated by work on Constantinople (Crapper 2020) and Pompeii (Monteleone et al 2021). These approaches are commended where there is sufficient physical evidence on which to base them.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst this research demonstrated the usefulness of river modelling software to simulate open channel flow in Roman aqueducts, the input data was so simple that the conclusions could offer only limited insight. Recently, however, the work has been extended by Ruggeri (2018) and Crapper (2020) to include consideration of the water available in the catchment, the intake configuration and seasonal variations, resulting in estimates of the flow reaching the city of Constantinople on a month-by-month basis, and insight into questions that archaeology alone has not been able to answer regarding the configuration of the fourth-and fifth-century aqueduct channels close to the city.…”
Section: C-flow In Water Systemsmentioning
confidence: 99%
“…2; another possible open cistern is tentatively identified with the cistern Modestiana at Saraçhane, Crow et alii 2008, 127. 30 Crow et alii 2008, 15; for the long distance channels see now Ruggeri 2018;Crapper (Forthcoming), and Crow (Forthcoming) for the bridges.…”
mentioning
confidence: 97%